A rare case of Merkel cell carcinoma presenting as a giant intra-thoracic mass: A case report and review of the literature. Issue 46 (November 2017) - Kong, Feng-Wei; Zhang, Miao; Wang, Heng; Lu, Cun-Tao; Wu, Wen-Bin; Liu, Yuan-Yuan
Abstract: Rationale: Merkel cell carcinoma (MCC) is an aggressive neuroendocrine-derived cutaneous cancer. Ectopic or single metastatic MCC located in thorax is extremely rare; meanwhile, its definite management has not been elucidated yet. Patient concerns: A 64-year-old female patient with a giant mass located in her left thorax was presented for stuffy pain of left chest for 6 months and fever for half a month. She underwent radical resection of vulvar MCC 10 years ago. Diagnoses: Computed tomography (CT)-guided biopsy of the intrathoracic mass revealed a diagnosis of MCC, without synchronous urogenital lesions on pelvic CT images. Interventions: This bulky tumor was completely resected via thoracotomy, along with the adjacent pulmonary lobe, pericardium, pleura, and diaphragm. Outcomes: The patient survived without local-regional recurrence or distant metastasis during the follow-up of 1 year up to now. Lessons: Ectopic or single metastatic MCC should be considered in the differential diagnosis of intrathoracic tumors, especially in patients with a history of MCC. Besides, a timely surgery combined with chemotherapy is effective for this disease.